Influence of crosspolarization of dual-polarized antenna elements on the ergodic capacity of a multichannel system - Ekaterina V. Averina; Ksenia V. Smuseva; Pavel A. Tokarev; Grigory K. Uskov (Физика волновых процессов и радиотехнические системы)
Background. Antenna arrays based on dual-polarization elements are used as radiating devices for modern and perspective radio communication systems. The main factor reducing the effectiveness of this approach is the presence of spatial correlation and cross-polarization between elements in the array. These effects can lead to a significant reduction in communication system capacity. Aim. Derive relationships based on the Kronecker model that allow to take into account the polarization properties of antenna elements when calculating the ergodic capacity of a multi-channel communication system. Investigate the influence of the cross-polarization parameter of the antenna element on the capacity. Assess the polarization characteristics of synthesized real antenna elements of various types and their impact on the capacity value. Methods. When deriving the basic relationships, methods of statistical radiophysics and electromagnetic analysis of the propagation channel were used. When synthesizing dual-polarization antenna elements, electrodynamic analysis methods based on Maxwell’s equations were used. Results. Based on the analysis using the derived relationships, it was established that the influence of the cross-polarization properties of the array antenna elements on the capacity of a multi-channel communication system becomes significant when the value of the cross-polarization parameters decreases below 10 dB. It is shown that synthesized real antenna elements of various types have high polarization isolation, which will lead to a slight decrease in the system capacity. Conclusion. The derived relationships and the developed methodology make it possible to estimate the change in the capacity of the communication system when taking into account the cross-polarization properties of the dual-polarization elements of the antenna array. This will allow to optimally select radiating elements for a given system. At the same time, the developed antenna elements of various types satisfy the imposed cross-polarization restrictions.